2016
DOI: 10.1037/prj0000182
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of strategies for successful weight loss in persons with serious mental illness participating in a behavioral weight loss intervention: A qualitative study.

Abstract: Objective The purpose of this study was to describe perceptions of weight loss strategies, benefits, and barriers among persons with serious mental illness who lost weight in the ACHIEVE behavioral weight loss intervention. Methods Semi-structured interviews with 20 ACHIEVE participants were conducted and analyzed using an inductive coding approach. Results Participants perceived tailored exercise sessions, social support, and dietary strategies taught in ACHIEVE – such as reducing portion sizes and avoidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 46 publications
(145 reference statements)
0
33
0
1
Order By: Relevance
“…Lastly, verbal or social persuasion refers to encouraging an individual and letting them know that they have the ability to perform the behavior, which can increase confidence and promote greater sustained effort to change. Social Cognitive Theory has informed numerous interventions for people with mental illness, including skills training (Patterson et al, 2006) and diabetes management and education (McKibbin et al, 2006) programs for middle-aged and older adults with schizophrenia, and lifestyle interventions for obese adults with serious mental illness (Aschbrenner, Naslund, & Bartels, 2016; Aschbrenner, Naslund, Shevenell, Mueser, & Bartels, 2016; Vazin et al, 2016). …”
Section: Health Behavior Theoriesmentioning
confidence: 99%
“…Lastly, verbal or social persuasion refers to encouraging an individual and letting them know that they have the ability to perform the behavior, which can increase confidence and promote greater sustained effort to change. Social Cognitive Theory has informed numerous interventions for people with mental illness, including skills training (Patterson et al, 2006) and diabetes management and education (McKibbin et al, 2006) programs for middle-aged and older adults with schizophrenia, and lifestyle interventions for obese adults with serious mental illness (Aschbrenner, Naslund, & Bartels, 2016; Aschbrenner, Naslund, Shevenell, Mueser, & Bartels, 2016; Vazin et al, 2016). …”
Section: Health Behavior Theoriesmentioning
confidence: 99%
“…Conversely, service providers believe clients experience positive support in adopting healthier lifestyle behaviors when clients take personal initiative, have peer support, and have easy access to community resources ( McKibbin et al, 2014 ; Browne et al, 2016 ; Naslund et al, 2016 ). Similarly, MHSUs have identified factors of empowerment, self-value and personal growth, social context and support, motivation and planning, and access as being important to engagement in healthy behaviors ( Graham et al, 2014 ; Vazin et al, 2016 ). These barriers and conversely lack of facilitators may account for lower rates of positive outcomes in service provider-delivered healthy lifestyle interventions ( Barre et al, 2011 ; Graham et al, 2013 ; Soundy et al, 2007 ).…”
mentioning
confidence: 99%
“…7,25,26 Moreover, complimenting the PCI with physical activity likely would result in better outcomes. 11,27 The results of this study come with several limitations. First, due…”
mentioning
confidence: 88%
“…[6][7][8] Prior studies have reported the effects of portion control to manage weight through education (eg, knowledge of nutrition), training in healthy eating practices (eg, increasing intake of fruits, vegetables, and water), support for behavioral changes, and action-oriented approaches (eg, grocery store visits, cooking demonstrations). 9,10 Moreover, a more recent study 11 demonstrates that reducing portion size is a useful weight loss strategy for people with SMI.…”
Section: Introductionmentioning
confidence: 99%